Description of Amplimerlinius uramanatiensis sp. n. (Nematoda: Merliniidae) and observations on three other species of the genus from Iran - Ghaderi, Reza; Karegar, Akbar (Zootaxa, 2014)
A new species of the genus Amplimerlinius  is described and illustrated from the rhizosphere of Vitis sp. from Kurdistan province in western Iran. A. uramanatiensis sp. n. is characterized by having seven to eight head annuli up to the end of the outer extension of the cephalic framework, 29–31 µm long stylet and cylindrical-clavate tail with a thin hyaline region (9–11 µm) and smooth terminus. Furthermore, A. paraglobigerus and A. macrurus were identified and intra-specific variability of A. globigerus was studied in detail, based on 21 populations collected from different regions of Iran. A key and diagnostic compendium to the species of the genus is provided.